Pola Komunikasi Antara Dosen Dan Mahasiswa Dalam Proses Pembelajaran Mata Kuliah Hubungan Internal Dan Eksternal - Rachel Mia L. Lumbantoruan; Evi Enitari Napitupulu; Noyanta Luga; Cyndi Samosir; Holy Zega (Universitas Sari Mutiara Indonesia, 2023)
Communication patterns between lecturers and students in this context become more important because they involve a higher level of knowledge transfer and a deeper understanding of communication. At the third semester level, students are expected to have better critical and analytical skills, and this is what makes effective communication very relevant. However, it should be recognized that there are variations in these communication patterns across higher education institutions. Researchers are interested in observing the teaching and learning process in internal and external relations courses so that this research is more specialized and focuses on one object. Apart from that, the researcher also observed that in the learning process, internal and external relations courses applied good communication patterns, as proven by class projects that had been created with the aim of making students understand more about the material, delivered with direct practice in the field. This research uses qualitative methods by conducting interviews with relevant lecturers and students. The results of the interview explain that the communication patterns used in the learning process for internal and external relations courses are upper and lower communication, meaning that the communication used is incorporated into organizational communication. This communication pattern is used to obtain feedback from students in the form of active response stimuli and implementation through practice in the field.